ClimUAd: Observation‐Based Gridded Daily Climate Data for Ukraine, 1946–2020 - Volodymyr Osadchyi; Oleg Skrynyk; Vladyslav Sidenko; Enric Aguilar; Jose Guijarro; Tamás Szentimrey; Olesya Skrynyk; Zita Bihari; Liudmyla Palamarchuk; Dmytro Oshurok; Igor Kravchenko; Dmytro Pinchuk (Geoscience Data Journal)
ABSTRACT In this work, we present results of the development of an observation‐based gridded climate dataset (ClimUAd), which covers the territory of Ukraine for the period of 1946–2020. The spatial resolution of the developed data is 0.1° × 0.1° (approximately 10 km in both longitude and latitude directions), with a 1‐day time step. Four essential climate variables are included in the dataset, namely daily sums of atmospheric precipitation and daily minimum, mean, and maximum air temperature. The created gridded product is based on the complete collection of station measurements performed at 178 weather stations in Ukraine. Quality control, homogenisation, and gridding of the station time series were performed by means of the widely used software, INQC, Climatol, and MISH, respectively. The created gridded time series were statistically compared with several existing datasets that have the same spatial resolution (i.e., previously developed gridded monthly data of Ukraine, ERA5‐Land and E‐OBS) on monthly and daily scales. The comparison showed good accordance with the Ukrainian monthly data (partly obtained from other paper sources than the daily data and homogenised with HOMER software) and acceptable agreement with ERA5‐Land and E‐OBS data. The developed data are of great importance as they were built with the involvement of as many real weather measurements as possible, representing a denser network than those included in continental/global gridded products. They can be used for regional climate monitoring and as the reference for a wide variety of climatological applications for the territory of Ukraine. The dataset is freely available for research purposes and can be downloaded from the data repository of the Ukrainian Hydrometeorological Institute.